Relationships among learning organizations, capital factors and organizational performance mediated by intrapreneurship in Iran insurance companies - Alipour, Farhad (2012)
There is empirical evidence to the importance of learning organizations and capital factors in organizational performance improvement. However, the result of this area is inconsistent and not much attention has been given to these factors in developing countries such as Iran. In addition, almost no effort has been made to examine the mediating effect of intrapreneurship in the relationship among learning organization, human capital, social capital, physical capital, and organizational performance. Therefore, the current study aims to develop a comprehensive model of the antecedents of organizational performance in the presence of intrapreneurship as a mediating variable. This study was done through a survey on 266 branches of Iranian insurance companies to predict the variables that affect organizational performance. In line with this objective, the SEM methodology was employed to present the best-fitted model. The fit indices show an acceptable fit for the proposed model. Therefore, the model was able to explain how independent (exogenous) variables (learning organization, human capital, social capital, physical capital) lead to organizational performance and how intrapreneurship mediates the relationship between these variables and organizational performance. Testing of the hypotheses was conducted using the correlation coefficient and Structural Equation Modeling (SEM). The overall findings show that there is a significant, linear, and positive relationship among learning organization, human capital, social capital, physical capital, intrapreneurship, and organizational performance. Also, the total effect (B)of these factors on organizational performance was .381, 307, 350, 250, and .242, respectively. One of the most significant findings that emerged from this study is that intrapreneurship has partially mediated the relationship between learning organization and organizational performance and the relationship between social capital and organizational performance. Therefore, companies should strengthen intrapreneurship behaviors as an alternative to increase organizational performance. Based on the findings, to increase entrepreneurial behaviors, organizations should focus especially on learning organization characteristics and social capital dimensions.